The effect of ginger (Zingiber officinale) extract on the neutrophil level and CAT (COPD Assessment Test) scores in workers with COPD due to dust exposure - Susilo Budi Pratama; Yuliani Setyaningsih; Daru Lestyanto (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACT Chronic obstructive pulmonary disease (COPD) is a progressive disease characterized by airflow limitation that does not fully return to normal and is associated with the increased inflammatory response in the airways due to exposure to noxious particles or gases. Workers are susceptible to exposure to steam, dust, gases, and fumes in the work environment. Administration of antioxidants can be beneficial in COPD patients by reducing oxidative stress to reduce the inflammatory response. Ginger contains various active ingredients that act as antioxidants. The research design is a quasi-experimental study with a pre-test and post-test approach. The research subjects were 30 subjects workers diagnosed with COPD. Subjects were divided into two groups: the control group was given standard therapy, the treatment group was given standard therapy and ginger extract. The treatment was given for one month, then the neutrophil and the COPD Assessment Test (CAT) scores were checked. The data were analyzed with an unpaired difference test. The treatment group (-5.67 +2.32) experienced more CAT decline than the control group (-0.73 +1.28) and showed a significant difference; this was evidenced in the unpaired difference test on the post-pre difference value (p = <0.001). The treatment group (-4.93 +4.43) experienced more neutrophil decline than the control group (0.27 +1.10) and showed a significant difference; this was evidenced in the unpaired difference test on the post-pre difference value (p = < 0.001). Administration of ginger extract can reduce neutrophil levels and CAT scores in COPD workers due to dust exposure. Keywords : COPD, CAT score, neutrophil, gingerCorrespondence : susilobudipratama@gmail.com